Pengembangan dan Pemanfaatan Desain Kemasan sebagai Media Promosi pada UKM Heavenine - I Gusti Ayu Desi Saryanti; Erlinda Mandasari; I Gusti Ayu Putri Indah Sidhiantari (Indonesian Journal Publisher, 2020)
Heavenine is one of the UKM which is engaged in the craft of making Balinese souvenirs. The products produced at this UKM are various kinds of Balinese souvenirs such as clothes, glass bags, umbrellas that have a characteristic Balinese image. Promotion is the one way to introduce products owned by a company or UKM. At this time, the promotion method carried out at UKM Heavenine is still fairly simple, promotions are carried out only around the region or by participating in exhibitions in one place so that there is a lack of breadth of the promotion network they have make the income is unstable. For this reason, the indicators of achievement in community service will be carried out by developing and utilizing packaging design as a promotional medium with the purpose of further expanding the trade network and increasing income for Heavenine UKM